051 The capture of a UK minimum data set for MS. Issue 6 (27th May 2022) - Nicholas, Richard; Craig, Elaine; Middleton, Rod; Ford, David; Tuite-Dalton, Katie; ,
Abstract : Background: The UK Multiple Sclerosis Register (UKMSR) was established in 2011 to capture 'real world' data from people with MS (pwMS) and the NHS. Capturing clinical data from the NHS for research is time consuming for clinical staff, can involve complicated governance, security and data quality issues. UKMSR has implemented quality controls, validation rules, new capture systems and site reporting to improve this. Method: Compare the Minimum Data Set (MDS) consisting of 7 items including demographics and EDSS for quality and quantity in the first 3 years (pilot phase) to the most recent 3 years of data capture Results: Completion of MDS (100% valid and completed values) (2011–2014) 4 sites, n=884. MDS received= 159 (17.9%), Time to add site ~3 Months (2017–2020) 48 Sites, n= 8836. MDS received = 5791 (65.5%), Time to add site ~6 Weeks Conclusion: The UKMSR has improved the clinical capture of MDS from a vastly increased number of patients and clinical sites. Improved validation standards and systems have increased data quality. Sites are added more quickly and rapidly notified of data quality issues for correction, making the data more useful to the site and ultimately of more utility to researchers. richard.nicholas@btinternet.com